The role of humans in the sustainability of marine ecosystems: A case study on the conservation of parrotfish and its ecological impact - Abdillah, Niko; Aziz, Cantika Liviona Dzikrina; Nugraha S., Yudi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Life is supported by the ecology and natural resources that exist on earth. Continents and oceans are the two main natural resources that host life and ecosystems around the world. 75% of the Earth's surface is covered by ocean waters that are rich in marine life. Although the oceans are vast, this does not mean that they are limitless. Population growth and development have led to an increase in the demand for marine resources. Increased demand and over-utilization of marine resources have led to strong pressures that have led to a decline in marine ecosystem services. Karimunjawa is famous for the natural beauty of its underwater coral reefs. Methods: This study employs a qualitative approach using literature and secondary data to examine the impact of parrotfish populations on coral reef sustainability. Findings: Based on current conditions, excessive catching of parrotfish has a negative impact on the sustainability of coral reefs in Karimunjawa National Park. It is necessary for local communities to understand the importance of the role of parrot fish for the sustainability of marine ecosystems. Parrotfish spend 90% of their time eating algae attached to coral reefs. Damage to the coral reef ecosystem causes coastal erosion in Karimunjawa National Park. Therefore, the role of the community in managing parrotfish resources is very necessary so as not to threaten the population for the sustainability of the marine ecosystem. Conclusion: The results of this research illustrate the role of humans, namely the community and tourists who come to Karimunjawa to carry out activities to preserve damaged coral reefs and create new coral reef areas. Novelty/Originality of this article: There are also government policies that must be considered and implemented properly for the sustainability of coral reef ecosystems and the conservation of parrotfish in Karimunjawa.